The Politics of Municipal Annexation: The Case of the City of London's Territorial Ambitions during the 1950s and 1960s - Meligrana, John (Urban History Review / Revue d'histoire urbaine, 2000)
Southern Ontario's local government system was under considerable stress immediately following the Second World War as rapid urban growth spilled over traditional municipal units. This situation generated a number of potential local government reforms. The paper focuses on the politics surrounding one type of reform, annexation. The London-Middlesex region is used as a case study to answer the question: why, how, and under what conditions did annexation come to dominate the regional political discourse? The paper examines the political tactics, procedures, and strategies that the City of London employed to support and articulate its territorial ambitions before the Ontario Municipal Board (OMB) and other forums during the 1950s and 1960s. London's 1961 annexation was the fiercest and final annexation battle that the OMB decided between the city and Middlesex County. The paper also unpacks the politics surrounding the 1961 annexation by reviewing the minutes of local council meetings, government reports, records of the OMB, and newspaper articles. It concludes that London's annexation success resulted from the city's superior political skills, a disorganized rural opposition, and the proceedings and operations of the OMB that divorced the issue of municipal boundaries from local governance, thereby biasing the outcome in favour of annexation.